2011
DOI: 10.4012/dmj.2011-046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic effects of six self-etching adhesives with direct and indirect contact tests

Abstract: This study evaluated the cytotoxicity of self-etching primers/adhesives by direct contact and dentin barrier tests. The three two-step self-etching systems Clearfil SE Bond (CSE), Clearfil Protect Bond (CPB), Prime&Bond NT/NRC (PB) and one-step self-etching systems Reactmer Bond (RB), Clearfil Tri-S Bond (CTS), and Adper Prompt L-Pop (AP) were examined. In direct contact tests, L929 cells were cultured in the presence of diluted solutions (50, 20, 10, and 1%) of primer/conditioner of adhesive systems. For dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…The structure and features of the monomers affect the cytotoxicity. In previous studies, the hydrophobic monomers Bis-GMA and UDMA have been reported to have more cytotoxic effects when compared to those of TEGDMA and HEMA 3,8,29,30) . In this study the bonding agent including UDMA (Group C) displayed the strongest cytotoxicity regarding the cell viability, while the bonding agent including HEMA (Group B) caused a lower decrease in cell viability as expected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The structure and features of the monomers affect the cytotoxicity. In previous studies, the hydrophobic monomers Bis-GMA and UDMA have been reported to have more cytotoxic effects when compared to those of TEGDMA and HEMA 3,8,29,30) . In this study the bonding agent including UDMA (Group C) displayed the strongest cytotoxicity regarding the cell viability, while the bonding agent including HEMA (Group B) caused a lower decrease in cell viability as expected.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the cytotoxicity of four different one-step, self-etching dentin bonding agents were analyzed with MTT assay, DCF assay, 8-OHdG measurement and comet assay in L929 mouse fibroblast cell culture model. The cytotoxicity of the resin based materials are related with dilution rate 3,27,28) . The tested dentin bonding agents had a dose-dependent (1:1>1:10>1:20) cytotoxic effect on L929 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under this condition, it was evident that the cytotoxicity of the dentine bonding agent was greatly attenuated by dentine discs, suggesting that dentine provided protective effects by interfering with the free diffusion of hazardous chemicals to the target cells. Therefore, it is expected that pulp tissue is minimally damaged, if at all, by bonding agents in clinical situations due to the presence of adequate amounts of dentine 10,11) . However, there are several bonding materials that still exert cytotoxic effects on pulp cells even in the presence of a dentine barrier 12) .…”
Section: Introductionmentioning
confidence: 99%